Características fisicoquímicas de tabletas de Diazepam 10 mg adquiridas por el estado peruano, Trujillo 2020 - Narro Alva, Claudia Beatriz (2020)
The aim of this research was to evaluate the physicochemical characteristics of Diazepam tablet 10 mg, coming from hospitals of Social Security (ESSALUD) and the Ministry of Health (MINSA) of Trujillo Province. In order to accomplish the objectives, the following physicochemical characteristics were determined: description of the product, average weight, breaking strength, dissolution test, identification and quantification of active principle. The results obtained are that the descriptive characteristics of the tablets obtained by the Peruvian state present a round shape, with convex faces, with a groove in one of its sides, light green color. The average weights of the samples are within the relative standard deviation with a value lower than 2%, except for sample 3. In the dissolution test, the average percentages of each lot fluctuate between 91.86% and 103.56 %. In the identification of active ingredient, the retention times of the samples analyzed are equal to those of the secondary standard solution diazepam with a value of 5.3 min. For the quantification of active ingredient by high performance liquid chromatography (HPLC), the declared quantity of this drug fluctuates between 99.67% to 102.08% per lot. Therefore, it is concluded that all the lots acquired by the Peruvian state comply with the physicochemical parameters established in the official norms, with the exception of the breaking force with an average relative standard deviation of 9.07%